Comparative Study on Structural, Electrical Transport and Magnetic Properties of Cr-Doped in Charge-Ordered Pr0.75Na0.25Mn1-Xcrxo3 and Nd0.75Na0.25Mn1-Ycryo3 Manganites - Zawawi, Rabiatul Adawiyah; Khairulzaman, Nurul Nasuha; Shamsuddin, Suhadir; Ibrahim, Norazila (International Journal of Engineering and Technology, 2018)
Cr doping in charge-ordered Pr0.75Na0.25Mn1-xCrxO3 and Nd0.75Na0.25Mn1-yCryO3 have been synthesized using conventional solid-state method to investigate its effect on structural, electrical transport and magnetic properties. X-ray diffraction (XRD) analysis for both compounds showed that the samples were crystallized in an orthorhombic structure with Pnma group. The unit cell volume valueÂ Â Â Â Â  decrease as the Cr-doped increased indicating the possibility of Mn3+ ion was replaced by Cr3+ due to the different of ionic radius. The temperature dependence of electrical resistivity showed an insulating behavior down to the lower temperature the both parent compound (x = 0 and y = 0). Successive substitution of Cr at Mn-site in Pr0.75Na0.25Mn1-xCrxO3 manganites induced the metal-insulator (MI) transition temperature around TMI~120 K and TMI~122 K for x = 0.02 and x = 0.04 samples respectively suggestively due to the enhancement of double-exchange (DE) mechanism as a result of suppress the CO state. Analysis of resistivity data of dlnÏ/dT-1 vs. T in Nd0.75Na0.25Mn1-yCryO3 manganite, showed a peak around 210 K and 160 K for y = 0 and 0.02 samples respectively while no peak was observed for y = 0.05 sample indicate the charge-ordered (CO) weakened. AC susceptibility, Ï‡â€™ measurements in Pr0.75Na0.25Mn1-xCrxO3 exhibits paramagnetic to ferromagnetic-like with curie temperature, TC increases from 132 K for x = 0.02 to 141 K for x = 0.04 with Cr content indicate the suppression of CO state meanwhile in Nd0.75Na0.25Mn1-yCryO3 showed paramagnetic to anti-ferromagnetic transition as Neel temperature TN increases from 115 K for y = 0.02 to 125 K for y = 0.05.